Permainan Tradisional untuk Perkembangan Kemampuan Sosial dan Emosional Anak Usia 5-6 Tahun - Miskiyah, Miskiyah; Nurhidaya, Andi Rezky; Ashar, Ashar (Ihya Ulum: Early Childhood Education Journal, 2025)
This study aims to understand how the implementation of traditional games supports the social and emotional development of early childhood children at TK Aisyiyah Bustanul Athfal Jatia, Gowa Regency.This study uses a qualitative approach with a descriptive method.The subjects of the study include the school principal, classroom teachers, and students.Data were collected through observation, interviews, and documentation to obtain a comprehensive picture of the implementation of traditional games in learning activities.The study findings indicate that traditional games play a crucial role in shaping children's social and emotional skills.After participating in traditional games, children learn to follow rules, cooperate in groups, and understand the concepts of sharing and effective communication.In addition, these games help children manage their emotions, boost their self-confidence, and build better social relationships with their peers.The implementation of traditional games at TK Aisyiyah Bustanul Athfal is carried out in a structured manner through learning planning, from annual programs to daily implementation plans.Therefore, this study emphasizes that traditional games can be an effective learning method in supporting early childhood development, and thus need to be continuously implemented and developed in children's education curricula.